Analisa Tingkat Keharmonisan Suami Istri Pengguna Vasektomi Dengan Algoritma C4.5 - ., Salamun; Yulianti, Wita (Universitas Atma Jaya Yogyakarta, 2018)
Abstract. Vasectomy may cause a strained relationship between a husband and wife. There are some causal factors such as communication, social, sexual, and economical factors. Male participation is an indicator of a successful family planning program (KB). The relevance of the participation of a male doing vasectomy is in his knowledge, behavior of vasectomy and the support from family. The purpose of this research is to reveal the relationship among the knowledge, attitude of KB male participant about vasectomy and the role of family support for vasectomy patient. This study is one way to observe the outcomes of government programs to reduce the number of the population Indonesia. The program may be considered as a way that can strain husband and wife relationship caused by various factors, such as communication, social, sexual and economic factors. In this study, the data is obtained from the official department of demography and national family planning (BKKBN) and based on the immediate observation of some couples who become the vasectomy patients. The data is then examined using C4.5 algorithms which will later make a decision tree which decide whether the couples will be fit or not for doing the vasectomy for family planning program.Keywords: KB, Vasectomy, C4.5 Algorithm.Abstrak. Vasektomi bisa mengakibatkan renggangnya suatu hubungan suami istri. Hal ini disebabkan oleh berbagai faktor seperti faktor komunikasi, sosial, seksual, dan ekonomi. Partisipasi pria menjadi indikator keberhasilan program Keluarga Berencana (KB). Keterkaitan partisipasi pria pengguna vasektomi adalah pengetahuan, tingkah laku partisipan KB pria tentang vasektomi, serta dukungan keluarga. Tujuan dari penelitian ini adalah untuk mengetahui hubungan pengetahuan, sikap akseptor/partisipan KB pria tentang vasektomi, serta peranan dukungan keluarga pengguna vasektomi. Penelitian ini merupakan salah satu cara untuk melihat hasil dari program pemerintah untuk mengurangi jumlah penduduk di Indonesia. Dalam penelitian ini, data didapatkan dari sebuah lembaga resmi KB yaitu Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) dan observasi lapangan secara langsung kepada beberapa pasangan suami istri yang menggunakan vasektomi. Data selanjutnya diolah menggunakan algoritma C4.5 yang hasilnya nanti akan menghasilkan pohon keputusan yang dapat menjawab apakah pasangan tersebut bisa mengikuti program KB vasektomi. Kata Kunci: KB, Vasektomi, Algoritma C4.5.